2013
DOI: 10.1002/jgrc.20345
|View full text |Cite
|
Sign up to set email alerts
|

Vortex waves and vertical motion in a mesoscale cyclonic eddy

Abstract: [1] Oceanic eddies are coherent mesoscale features present anywhere in the World Ocean. The vertical motion associated with eddies plays a fundamental role in the ocean circulation and ocean-atmosphere interaction. Eddies also transport phytoplankton and modify the nutrient fluxes from the deep layers into the euphotic zone, affecting open ocean primary production and potentially influencing the global carbon cycle. However, vertical exchanges driven by mesoscale eddies cannot be directly measured. Here, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 57 publications
9
37
0
Order By: Relevance
“…Several studies have estimated typical vertical velocities of about 10 m/day within mesoscale structures (Barceló‐Llull et al, ; Martin & Richards, ; Nardelli et al, ). However, Nardelli () has already calculated intense vertical velocities, larger than 100 m/day within a mesoscale eddy in the Agulhas Current, similarly to those estimated in our case study. Moreover, the adiabatic QG ω ‐equation has shown consistent structures, at about 50‐km scale, and a good agreement with the patterns of vertical velocities computed from primitive equation model outputs (Nardelli et al, ) although the intensities differ slightly from the modeled ones.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several studies have estimated typical vertical velocities of about 10 m/day within mesoscale structures (Barceló‐Llull et al, ; Martin & Richards, ; Nardelli et al, ). However, Nardelli () has already calculated intense vertical velocities, larger than 100 m/day within a mesoscale eddy in the Agulhas Current, similarly to those estimated in our case study. Moreover, the adiabatic QG ω ‐equation has shown consistent structures, at about 50‐km scale, and a good agreement with the patterns of vertical velocities computed from primitive equation model outputs (Nardelli et al, ) although the intensities differ slightly from the modeled ones.…”
Section: Discussionsupporting
confidence: 87%
“…The vertical motions, generated in mesoscale (or submesoscale) features, structures with space scales of the order of (or smaller than) the typical value of the Rossby radius in the Mediterranean Sea (∼10 km; Grilli & Pinardi, ; Pascual et al, ) can play a key role for primary production by supplying nutrients to the upper layers (Martin et al, ; Lévy et al, ). Different physical processes are known to cause vertical motions within mesoscale structures: deformations of the flow and spatial inhomogeneities (Giordani et al, ), eddy perturbation (Martin & Richards, ; Nardelli, ; Pilo et al, ), linear Ekman pumping (McGillicuddy et al, ; Gaube et al, ), or eddy‐wind interactions (McGillicuddy et al, ). However, the study of these vertical motions is still very challenging as those features, and their interactions with biogeochemistry are hard to sample (Mahadevan & Tandon, ; Mahadevan, ; McGillicuddy, ) but also because direct measurements of vertical velocities are not yet possible.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that an important assumption adopted by Zhang et al [2013] is the axisymmetry of eddies' horizontal fields, i.e., p 0 (x,y,z) 5 R(r)H(z), where r is the radial distance to the eddy center. Though there are indeed departures from axisymmetric circle observed for individual mesoscale eddies [Buongiorno-Nardelli, 2013;Pidcock et al, 2013], the amplitude of the departure was found usually relatively small, about 20%-25% of the axisymmetric part, as estimated by altimetry observations [Chelton et al, 2011a]. Hence, it is not unreasonable to make the asymmetric assumption, and its correctness can be supported by theoretical argument and indirectly verified by observations of atmospheric synoptic eddies in following sections.…”
Section: Methodsmentioning
confidence: 62%
“…Horizontal divergence (Figure c) also shows an interesting pattern with patches of positive divergence at the south‐west and north‐east corner of the structure, rather than at the center, as would be expected from a traditional conceptual model of eddy‐pumping. This is in agreement with Nardelli [] who showed most intense vertical velocities at the periphery of a mesoscale cyclonic eddy. The asymmetry of the CCE also creates a zone of enhanced particle dispersion aligned with the eddy's major axis over the 1000 m topographic contour, as indicated by high values of IROS parameter (Figure b).…”
Section: Kinematics and Dynamic Variabilitymentioning
confidence: 99%